Ultra-fast intramolecular vibronic coupling revealed by RIXS and RPES maps of an aromatic adsorbate on TiO2(110) - O'Shea, James N.; Handrup, Karsten; Temperton, Robert H.; Gibson, Andrew J.; Nicolaou, Alessandro; Jaouen, Nicolas; Taylor, John B.; Mayor, Louise C.; Swarbrick, Janine C.; Schnadt, Joachim (American Institute of Physics, 2018)
Two-dimensional resonant inelastic x-ray scattering (RIXS) and resonant photoelectron spectroscopy (RPES) maps are presented for multilayer and monolayer coverages of an aromatic molecule (bi-isonicotinic acid) on the rutile TiO2(110) single crystal surface. The data reveals ultra-fast intramolecular vibronic coupling upon core-excitation from the N 1s orbital into the lowest unoccupied molecular orbital (LUMO) derived resonance. In the RIXS measurements this results in the splitting of the participator decay channel into a purely elastic line which disperses linearly with excitation energy, and a vibronic coupling channel at constant emission energy. In the RPES measurements the vibronic coupling results in a linear shift in binding energy of the participator channel as the excitation is tuned over the LUMO-derived resonance. Localisation of the vibrations on the molecule on the femtosecond timescale results in predominantly inelastic scattering from the core-excited state in both the physisorbed multilayer and the chemisorbed monolayer.